2022
DOI: 10.3389/fnagi.2021.723405
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Minor Hallucinations in Chinese Parkinson's Disease Patients

Abstract: BackgroundPsychotic symptoms are common in Parkinson's disease (PD). However, the clinical characteristics of PD psychosis (PDP) have been rarely reported in Chinese PD patients. We aimed to categorize PDP in a PD cohort and its relationship to other clinical characteristics.MethodsA total of 149 Chinese PD patients were consecutively enrolled, and idiopathic PD patients were recruited in the study. The symptoms of PDP were assessed with the enhanced Scale for the Assessment of Positive Symptoms in PD. Then, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…The prevalence of illusions, passage phenomena, feeling of presence, or any minor phenomenon was high in participants with and without PD, but as expected was significantly higher in the PD group. Among those with PD, the overall prevalence of minor phenomena (43%) and isolated minor phenomena (18%) was consistent with other studies that have reported a 20%–45% prevalence 2,612 and 12%–28% prevalence, 2,8,11,12,15 respectively. In our study, the most commonly reported type of minor phenomenon was passage phenomena (38%), followed by illusions (14%), and feeling of presence (10%), whereas other studies have reported 8%–38% prevalence for passage phenomena, 4%–27% for illusions, and 4%–33% for feeling of presence.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The prevalence of illusions, passage phenomena, feeling of presence, or any minor phenomenon was high in participants with and without PD, but as expected was significantly higher in the PD group. Among those with PD, the overall prevalence of minor phenomena (43%) and isolated minor phenomena (18%) was consistent with other studies that have reported a 20%–45% prevalence 2,612 and 12%–28% prevalence, 2,8,11,12,15 respectively. In our study, the most commonly reported type of minor phenomenon was passage phenomena (38%), followed by illusions (14%), and feeling of presence (10%), whereas other studies have reported 8%–38% prevalence for passage phenomena, 4%–27% for illusions, and 4%–33% for feeling of presence.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the most commonly reported type of minor phenomenon was passage phenomena (38%), followed by illusions (14%), and feeling of presence (10%), whereas other studies have reported 8%-38% prevalence for passage phenomena, 4%-27% for illusions, and 4%-33% for feeling of presence. 2,7,8,11,15,16 The wide range in prevalence estimates likely reflects methodological differences, including disease and treatment characteristics of the study sample (eg, some excluded individuals with cognitive impairment or antipsychotic medication use), methods of ascertainment, time periods under evaluation, and definitions (eg, some studies narrowly defined passage phenomena as the perception of a person or animal). Our study was unique in that it also systematically assessed the prevalence of non-visual illusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among our PD patients, the presence of hallucinations was significantly associated with older age, more severe motor and non-motor symptoms, such as HY stage, UPDRS-III score, depression, anxiety, impaired cognition and sleep disturbances. Multivariate analysis identified two clinical variables, the NMSQ score and MOCA score, as independent risk factors for hallucinations, supported by the results of similar studies ( 4 , 27 ). Overall, as PD progressed, the motor symptoms became more severe and non-motor symptoms, including hallucinations and sleep disturbances, became more complex.…”
Section: Discussionsupporting
confidence: 71%